Metastatic potential of small and minimally invasive breast carcinomas - Sinn, Peter; Oelmann, Arne; Anton, Hans-Werner; Diel, Ingo J. (Virchows Archiv, 1994)
Invasive ductal mammary carcinomas (IDC) of 1 cm in tumour size or less account for less than 20% of all IDC. We have observed 167 such cases at our Institution between 1985 and 1989. These were divided into carcinomas with an extensive or predominant intraductal component (EIC or PIC, being least 2× or 4× larger than the invasive component; 90) and compared statistically with the control group (no EIC or PIC; 77) for known prognostic factors and for their metastatic behaviour. Lymph nodes were step sectioned in order to detect occult micrometastases. The median follow up time was 62.6 months. Lymph node metastases were seen in 10% of pT1a and 19% of pT1b cases. Significant differences were found when comparing the EIC/PIC group with the control group (pT1a: 11% vs. 0%, pT1b: 37% vs. 11% lymph node metastases). Also, axillary and infraclavicular recurrence rates were higher for EIC/PIC carcinomas compared with other IDC of ≤1 cm (9.3% vs. 4.2%). This significantly adverse metastatic behaviour of the EIC/PIC tumours may be in part due to the more frequent occurrence of multifocal tumours in this group (in 43% vs. 6%), resulting in a greater tumour burden. We conclude that the overall risk of lymph node metastasis is not negligible in carcinomas of 1 cm or less in diameter with the risk being more than doubled for carcinomas with an intraductal component exceeding the invasive tumour by a factor of two. These differences were relevant only to regional metastases; the risk for distant metastasis and survival was identical after 5 years.